Pendampingan Perencanaan Jalur Interpretasi Wisata Trekking di Desa Cisaat, Kecamatan Ciater, Kabupaten Subang, Jawa Barat - Abidin, Jenal (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Assistance for Planning Interpretation of Trekking Tourism Routes in Cisaat Village, Ciater District, Subang Regency, West Java Cisaat Tourism Village has various attractive potentials to be used as a tourist attraction in the form of its people's natural and cultural potential. Cisaat Tourism Village began to receive public attention since it received appreciation as one of the villages included in the tourism village assistance program from the Ministry of Tourism and Creative Economy. visits to Cisaat Village experienced a significant increase while the products and tourism activities were still limited. There is a need for tourism efforts in Cisaat Village to meet the increasing demand for tourists from different segments of the tourism market. This Community Service Program is carried out to develop the potential of natural landscapes into trekking tourism products in Cisaat Village. Through workshops and training, this is carried out using situational analysis methods, problems, and problem-solving plans. The development of trekking tourism can be offered as a new alternative to tourism in Cisaat Village to capture individual or small-group market segmentation. Potential resources and natural and cultural landscapes related to the development of trekking tourism are already available. However, the understanding, abilities, and attitudes possessed by human resources are still not sufficient. Assistance activities for making trekking tourism interpretation paths are expected to increase the institutional capacity of tourist villages in products, tourist attractions, and capabilities in organizing trekking tours.